Rationales for discontinuation of disease-modifying antirheumatic drugs, biologic agents, and tofacitinib in rheumatoid arthritis - Yu. V. Muraviev; G. I. Gridneva; L. A. Muravieva; N. V. Muravieva; A. V. Alexeeva; K. S. Nurbaeva; K. M. Mikhailov; A. V. Rozov (Современная ревматология)
Objective: to analyze the reasons for discontinuation of traditional disease-modifying antirheumatic drugs (tDMARDs), biologic agents (BAs), and tofacitinib (TOFA) in patients with rheumatoid arthritis (RA) in real clinical practice.Patients and methods. The authors carried out a retrospective analysis of the data of the patients treated with tDMARDs, BAs, and TOFA, who had been included by the physicians of the V.A. Nasonova Research Institute of Rheumatology (RIR) in the all-Russian register of patients with RA (Group 1) in January 1, 2016 to November 1, 2018, the data of a pharmacology history (information about inefficacy (IE) and adverse reactions (ARs) due to the use of tDMARDs and BAs) in RA patients admitted to the V.A. Nasonova RIR during 2011–2016 for high-tech medical care (Group 2).Results. The main reasons for discontinuation of tDMARDs, BAs, and TOFA were found to be their IE and ARs.Discussion. 20% of patients with early RA never achieve not only remission, but also minimal disease activity, despite the introduction of current guidelines for its treatment. It is believed that one of the potential causes of resistance to treatment in RA is the IE of traditionally used drugs, which is mediated by transporters (ABCB1 and ABCG2) that reduce their concentrations, causing outflow from the intracellular space. The great importance of these transporters in RA is that their substrates are widely used drugs, such as methotrexate, leflunomide, sulfasalazine, aminoquinoline drugs, and prednisolone. The function of ABCB1 and ABCG2 is shown to be increased in patients with active RA, i.e. the disease activity is closely related to this phenomenon.Conclusion. IE and ARs are the most common reasons for discontinuation of tDMARDs, BAs, and TOFA in patients with RA; further investigations are needed to clarify their possible mechanisms.Objective: to analyze the reasons for discontinuation of traditional disease-modifying antirheumatic drugs (tDMARDs), biologic agents (BAs), and tofacitinib (TOFA) in patients with rheumatoid arthritis (RA) in real clinical practice.Patients and methods. The authors carried out a retrospective analysis of the data of the patients treated with tDMARDs, BAs, and TOFA, who had been included by the physicians of the V.A. Nasonova Research Institute of Rheumatology (RIR) in the all-Russian register of patients with RA (Group 1) in January 1, 2016 to November 1, 2018, the data of a pharmacology history (information about inefficacy (IE) and adverse reactions (ARs) due to the use of tDMARDs and BAs) in RA patients admitted to the V.A. Nasonova RIR during 2011–2016 for high-tech medical care (Group 2).Results. The main reasons for discontinuation of tDMARDs, BAs, and TOFA were found to be their IE and ARs.Discussion. 20% of patients with early RA never achieve not only remission, but also minimal disease activity, despite the introduction of current guidelines for its treatment. It is believed that one of the potential causes of resistance to treatment in RA is the IE of traditionally used drugs, which is mediated by transporters (ABCB1 and ABCG2) that reduce their concentrations, causing outflow from the intracellular space. The great importance of these transporters in RA is that their substrates are widely used drugs, such as methotrexate, leflunomide, sulfasalazine, aminoquinoline drugs, and prednisolone. The function of ABCB1 and ABCG2 is shown to be increased in patients with active RA, i.e. the disease activity is closely related to this phenomenon.Conclusion. IE and ARs are the most common reasons for discontinuation of tDMARDs, BAs, and TOFA in patients with RA; further investigations are needed to clarify their possible mechanisms.